If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 4 = 5x + -12 Reorder the terms: 4 + x = 5x + -12 Reorder the terms: 4 + x = -12 + 5x Solving 4 + x = -12 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 4 + x + -5x = -12 + 5x + -5x Combine like terms: x + -5x = -4x 4 + -4x = -12 + 5x + -5x Combine like terms: 5x + -5x = 0 4 + -4x = -12 + 0 4 + -4x = -12 Add '-4' to each side of the equation. 4 + -4 + -4x = -12 + -4 Combine like terms: 4 + -4 = 0 0 + -4x = -12 + -4 -4x = -12 + -4 Combine like terms: -12 + -4 = -16 -4x = -16 Divide each side by '-4'. x = 4 Simplifying x = 4
| 3cos^2(6x)-8cos(3x)+5=0 | | -x+8+6x=53 | | 6x-x=-26+11 | | -4x-8+3x=-20 | | x+88-5x=40 | | -x+5-4x=-50 | | 3(9x-6/5) | | x^2-3.5x+10=0 | | 11=-6x+5x+8 | | 4Xw= | | 2/4a=-4/2 | | 14xw= | | T-22=0 | | (-1+y)+3y=11 | | 51=3u+12 | | 4x-12-3x+6=-48-12 | | v-6.5=7.26 | | u-9.66=6.36 | | (11x+6y)+(38x+22y)= | | 7+6x+7x=33 | | -5+a-8= | | u+5.2=7.94 | | 3x-(x-3)=2(x+1)+2 | | 5s-39=76 | | -131=7x+7x+9 | | 3x-2/3-2x-5/5=7/15 | | 12xm=104 | | X/5-x-7/3=1/3 | | 3a-4=9+12 | | 1+2x=23 | | 50-8x=2 | | 7(4x-3)=-21 |